Question:
A translation is applied to the triangle where A(1, 4) , B(2, -2) , and C(-3, 2). The image is the triangle that has vertices A′(5, 4) , B′(6, -2) , and C′(1, 2).
Answer:
![(x + 4,y)](https://tex.z-dn.net/?f=%28x%20%2B%204%2Cy%29)
Step-by-step explanation:
Given
![A = (1,4)\\B = (2,-2)\\C = (-3,2)](https://tex.z-dn.net/?f=A%20%3D%20%281%2C4%29%5C%5CB%20%3D%20%282%2C-2%29%5C%5CC%20%3D%20%28-3%2C2%29)
![A' = (5,4)\\B' = (6,-2)\\C' = (1,2)](https://tex.z-dn.net/?f=A%27%20%3D%20%285%2C4%29%5C%5CB%27%20%3D%20%286%2C-2%29%5C%5CC%27%20%3D%20%281%2C2%29)
From the translation of triangle ABC to A'B'C',
It will be observed that the y coordinates of both triangle remain unchanged.
This implies that triangle ABC is translated on the x coordinates alone.
Considering the x coordinates of A and A', we have:
![1 + k = 5](https://tex.z-dn.net/?f=1%20%2B%20k%20%3D%205)
Make k the subject
![k = 5 - 1](https://tex.z-dn.net/?f=k%20%3D%205%20-%201)
![k = 4](https://tex.z-dn.net/?f=k%20%3D%204)
When 4 is added to the x coordinates of B and C, it gives the x coordinates of B' and C'.
Hence, the rule of translation is:
![(x + 4,y)](https://tex.z-dn.net/?f=%28x%20%2B%204%2Cy%29)